Cosmoe's Wiener getaway - Brallier, Max (Brallier, Max Galactic hot dogs, 2015)
Meet Cosmoe, the Earth-Boy. He's captain of the Neon Weiner, the finest flying food truck in the galaxy. Along with his bud, Big Humphree, he spends his days cruising the cosmos and staying crazy busy